2007
DOI: 10.1007/s11104-007-9220-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of understory removal, N fertilization, and litter layer removal on soil N cycling in a 13-year-old white spruce plantation infested with Canada bluejoint grass

Abstract: Canada bluejoint grass [Calamagrostis canadensis (Michx.) Beauv., referred to as bluejoint below] is a competitive understory species widely distributed in the boreal region in North America and builds up a thick litter layer that alters the soil surface microclimate in heavily infested sites. This study examined the effects of understory removal, N fertilization, and litter layer removal on litter decomposition, soil microbial biomass N (MBN), and net N mineralization and nitrification rates in LFH (the sum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 44 publications
0
47
1
Order By: Relevance
“…Understory functioning as a habitat for animals thus contributing to forest biodiversity has also been reported (Camprodon and Brotons 2006). However, the impact of understory on soil ecosystems has been studied less and focused mainly on soil nitrogen (N) mineralization and N cycling (Tripathi et al 2005;Matsushima and Chang 2007). Due to high turnover rates, understory vegetation has been suggested to contribute substantially to nutrient cycling and soil fertility (Yarie 1980;Chapin III 1983;Nilsson and Wardle 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Understory functioning as a habitat for animals thus contributing to forest biodiversity has also been reported (Camprodon and Brotons 2006). However, the impact of understory on soil ecosystems has been studied less and focused mainly on soil nitrogen (N) mineralization and N cycling (Tripathi et al 2005;Matsushima and Chang 2007). Due to high turnover rates, understory vegetation has been suggested to contribute substantially to nutrient cycling and soil fertility (Yarie 1980;Chapin III 1983;Nilsson and Wardle 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies have found that removal of understory plants led to significant increase in soil N content [49,50] and soil water availability [12,51], and consequently, resulted in increased growth rate of the overstory trees [6,51]. The present study provided insight to explain the functional mechanisms underlying the positive effects of understory-removal on overstory growth.…”
Section: Discussionmentioning
confidence: 51%
“…Hence, the understory may be most likely to affect the overstory through below ground competition for soil resources [48]. For example, dense understory vegetation can significantly decrease the soil temperature, net N mineralization, net nitrification rates, and soil water availability [12]. Removal experiments showed that understory removal can lead to significant increases in soil N [49,50] and soil water availability [12,51], and consequently, result in increased growth rate of the overstory trees [6,51].…”
Section: Dry Season Vs Wet Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…The litera ture about the effect of understory vegetation on the water availability of overstory trees is sparse. One study has shown that dense understory vegetation can significantly decrease soil-water availability (Matsushima & Chang 2007). An optimal stand density and removing of shrubs might improve water availability and reduce risks of cavitation for trees and thus have a positive effect on sto matal opening and consequently on carbon uptake.…”
Section: Implications For the Future And The Role Of Forest Managementmentioning
confidence: 99%